Belomor: Criminality and Creativity in Stalin’s Gulag - Draskozcy, Julie S. (Myths and Taboos in Russian Culture, 2014)
Containing analyses of everything from prisoner poetry to album covers, Belomor: Criminality and Creativity in Stalin’s Gulag moves beyond the simplistic good/evil paradigm that often accompanies Gulag scholarship. While acknowledging the normative power of Stalinism—an ethos so hegemonic it wanted to harness the very mechanisms of inspiration—the volume also recognizes the various loopholes offered by artistic expression. Perhaps the most infamous project of Stalin’s first Five-Year Plan, the Belomor construction was riddled by paradox, above all the fact that it created a major waterway that was too shallow for large crafts. Even more significant, and sinister, is that the project won the backing of famous creative luminaries who enthusiastically professed the doctrine of self-fashioning. Belomor complicates our understanding of the Gulag by looking at both prisoner motivation and official response from multiple angles, thereby offering a more expansive vision of the labor camp